The Development of Learning Activites using Historical Method on An Ancient Word Civilizations for Matthayomsuksa 5 Student - Keawweha, Pratchaya; Suikraduang , Arun (Journal for Developing the Social and Community, 2024)
The objective of this research is as follows: (1) To enhance the learning activities using historical methods regarding ancient world civilizations among 5th-year high school students, aiming for an efficiency criterion of 85/85. (2) To compare the academic performance of 5th-year high school students studying via historical learning activities before and after the implementation. (3) To compare the analytical thinking abilities of 5th-year high school students before and after studying via historical learning activities. 4) To examine the satisfaction level of 5th-year high school students regarding the implementation of historical learning activities. The sample group consists of 40 students from 5/8 grade in the first semester of the academic year 2566 at Sri Kranuan Wittayakom School, Kranuan District, Khon Kaen Province. The selection method used was group randomization. Tools used in the research included historical learning activity plans, performance assessment tests, analytical thinking ability assessments, satisfaction questionnaires, and data analysis through means, percentages, standard deviations, and t-tests. The research findings indicate that: (1) The historical learning activity plan for History subject, 5th-year high school, has an efficiency rating of 85.71/86.50. (2) The academic performance in History subject of 5th-year high school students after engaging in historical learning activities is significantly higher than before, with statistical significance at the .05 level.(3) The analytical thinking abilities of 5th-year high school students after participating in historical learning activities are significantly higher than before, with statistical significance at the .05 level. And 4) students express the highest level of satisfaction towards the implementation of historical learning activities.